Rayleigh wave propagation along an irregular free surface - Gan, Yifan (Nanyang Technological University, 2024)
This research aims to investigate the impact of an irregular free surface on the propagation of Rayleigh-type surface waves. The factors of irregularity considered include amplitude, wavelength, and shape. The primary method employed in this study is finite element analysis using COMSOL Multiphysics. We established and analyzed models in three groups, each with varying parameters, across time, frequency, and eigenfrequency domains. The main reason for the observed attenuation is that irregularities alter surface waves' reflection and transmission ratios. Our findings reveal that irregularities in amplitude, wavelength, and shape affect the propagation of Rayleigh surface waves in different ways. Generally, smaller irregularity wavelengths lead to increased reflection, while higher amplitude ratios result in larger reflection ratios. Among the four shapes analyzed, square shapes have the most significant impact on propagation in both time and frequency domains. Additionally, irregularity amplitude is found to be the most influential factor in dispersion. This research numerically reveals the trends in Rayleigh-type surface wave propagation along irregular free surfaces and may inform the design of surface shapes to optimize Rayleigh wave propagation.